2013
DOI: 10.1111/cge.12224
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the phenotypic spectrum of ECEL1‐related congenital contracture syndromes

Abstract: Using a combination of homozygosity mapping and whole-exome sequencing, we identified a novel missense c.1819G>A mutation (S607G) in the endothelin-converting enzyme-like 1 (ECEL1) gene in a consanguineous pedigree of Turkish origin presenting with a syndrome of camptodactyly, scoliosis, limited knee flexion, significant refractive errors and ophthalmoplegia. ECEL1 mutations were recently reported to cause recessive forms of distal arthrogryposis. This report expands on the molecular basis and the phenotypic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 31 publications
(55 reference statements)
3
33
1
Order By: Relevance
“…Previous clinical studies have reported that mutations of human homologue ECEL1 are responsible for DA, and DA patients usually display multiple contractures, especially in the upper limbs (i.e., hand, wrist, and elbow contractures) and lower limbs (i.e., foot, ankle, knee, and hip joint contractures) [9,19,27,28]. Although the pathogenesis of the disease remains poorly understood, our systematic Fig.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Previous clinical studies have reported that mutations of human homologue ECEL1 are responsible for DA, and DA patients usually display multiple contractures, especially in the upper limbs (i.e., hand, wrist, and elbow contractures) and lower limbs (i.e., foot, ankle, knee, and hip joint contractures) [9,19,27,28]. Although the pathogenesis of the disease remains poorly understood, our systematic Fig.…”
Section: Discussionmentioning
confidence: 79%
“…The ECEL1 mutation is observed in type DA5, which is largely characterized by ocular phenotypes (ptosis, ophthalmoplegia, and/or strabismus), in addition to the limb contracture phenotypes common to other DA types. In terms of these ocular phenotypes, two reports have suggested that ECEL1 mutation also leads to congenital cranial dysinnervation disorders (CCDD), which are the result of developmental errors in cranial musculature innervation [16,27]. Because DINE is expressed in all cranial and spinal motoneurons from early embryonic stages in rodents [20], cranial motor innervations could also be affected by a deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter findings were corroborated by both Human Splicing Finder and CADD, which yielded a PHRED scaled score of 24.8. Numerous mutations in the ECEL1 gene have been reported recently, and, with the spectrum of clinical features of the associated condition, DA5D is becoming more established with each one [6][7][8] . Many of the characteristic features of DA5D are present in this reported case.…”
Section: Discussionmentioning
confidence: 99%